Evaluation of the Rate of Data Transfer, Learning, and Ease of Access to Data via Data Visualization in Virtual Medical Courses from the Viewpoint of Teachers and Students in Shahid Beheshti University of Medical Sciences - Elaheh Amirmahani; Adel Soleimani Nejad (Kerman University of Medical Sciences, 2018)
Background Data visualization refers to the methods of data presentation in visual formats using specific technologies, which can present data through a visual process with better understanding and recognition. The current study aimed at evaluating the rate of data transfer, learning, and ease of access to data through data visualization in virtual learning systems. Methods The current survey was conducted on 131 students and teachers of virtual medical courses at Shahid Beheshti University of Medical Sciences as the statistical population in the academic year 2015 - 2016. Of the study population, 79 subjects were selected using the simple random sampling method. Data collection tool was a 28-item researcher-made questionnaire, which its reliability was confirmed by the Cronbach's alpha 0.82. Results Based on the results of the current study, data visualization could significantly affect virtual learning in the students. In addition, data visualization improved productivity indices as well as rate of data transfer, learning, and ease of access to data among students and teachers. Conclusions Based on the results of the current study, it is recommended that data visualization be used in educational programs at all grades and courses in order to benefit from its advantages in improving productivity, rate of data transfer, learning, and ease of access to data among students and teachers of universities and institutes.